SOSIALISASI PENTINGNYA ADMINISTRASI KEPENDUDUKAN MELALUI PENGGUNAAN APLIKASI SITEPAK - Ayudyarini, Shifa; Pujihastuti, Isti; Rofieq, Ainur (An-Nizam, 2023)
Population administration is a series of activities for structuring and controlling the publication of population documents and data through population registration, civil registration, management of population administration information. Population Administration is used to collect and process data which will later be used for preparation or planning for certain activities or other things. This means that administration is used to organize and establish communication between members in an organization. With current technological advances that can make life easier, especially in services to the community. Advances in technology in services such as the SITEPAK web site which has been provided by the Bekasi Regency government play a very important role in making it easier for every community member who wants to update or create population data. From the results of this activity, it can be concluded that the understanding of the community and Karang Haur Village officials regarding the use of the SITEPAK application is still lacking and needs to be improved regarding services that require less time and distance. Therefore, by holding this socialization, it is hoped that it can increase public understanding of the importance of Population Administration through the SITEPAK application.